Coupled atmosphere–ocean observations of a cold‐air outbreak and its impact on the Iceland Sea. (27th January 2023) - Renfrew, Ian A.; Huang, Jie; Semper, Stefanie; Barrell, Christopher; Terpstra, Annick; Pickart, Robert S.; Våge, Kjetil; Elvidge, Andrew D.; Spengler, Thomas; Strehl, Anna‐Marie; Weiss, Alexandra
Abstract: Marine cold‐air outbreaks (CAOs) are vigorous equatorward excursions of cold air over the ocean, responsible for the majority of wintertime oceanic heat loss from the subpolar seas of the North Atlantic. However, the impact of individual CAO events on the ocean is poorly understood. Here we present the first coupled observations of the atmosphere and ocean during a wintertime CAO event, between 28 February and 13 March 2018, in the subpolar North Atlantic region. Comprehensive observations are presented from five aircraft flights, a research vessel, a meteorological buoy, a subsurface mooring, an ocean glider, and an Argo float. The CAO event starts abruptly with substantial changes in temperature, humidity and wind throughout the atmospheric boundary layer. The CAO is well mixed vertically and, away from the sea‐ice edge, relatively homogeneous spatially. During the CAO peak, higher sensible heat fluxes occupy at least the lowest 200 m of the atmospheric boundary layer, while higher latent heat fluxes are confined to the surface layer. The response of the ocean to the CAO is spatially dependent. In the interior of the Iceland Sea the mixed layer cools, while in the boundary current region it warms. In both locations, the mixed layer deepens and becomes more saline. Combining our observations with one‐dimensional mixed‐layer modelling, we show that in the interior of the Iceland Sea, atmospheric forcing dominates the ocean response. In contrast, in the boundary current region lateral advection and mixing counteract the short‐term impact of the atmospheric forcing. Time series observations of the late‐winter period illustrate a highly variable ocean mixed layer, with lateral advection and mixing often masking the ocean's general cooling and deepening response to individual CAO events. Abstract : Simultaneous observations of the atmosphere and ocean during a cold‐air outbreak over the Iceland Sea. The top panel shows near‐surface potential temperature from two research flights and a research vessel at the onset of the event; the distribution is relatively homogeneous, although affected by the sea‐ice off the East Greenland coast. The bottom panel shows observed ocean mixed‐layer depth during the first part of the event; the response of the ocean is spatially dependent due to counteracting vertical and lateral processes.